HIGH INTENSITY HYPOLIPIDEMIC THERAPY AND DECREASED LEVEL OF LOW DENSITY LIPOPROTEIDES CHOLESTEROL: IS THE APPROACH JUSTIFIED? POINT OF VIEW - M. G. Bubnova (Российский кардиологический журнал, 2018)
The review is focused on the issue of high-intensity treatment. The evidence provided, on efficacy of statins prescription in high intensity regimen to patients with very high cardiovascular risk. Indications outlined for this type of therapy in primary and secondary prevention practice. Problems of tolerability and safety also considered.